APOGEE view of the globular cluster NGC 6544. Issue 3 (16th April 2021) - Gran, F; Zoccali, M; Rojas-Arriagada, A; Saviane, I; Contreras Ramos, R; Beaton, R; Bizyaev, D; Cohen, R E; Fernández-Trincado, J G; García-Hernández, D A; Geisler, D; Lane, R R; et al.
ABSTRACT: The second phase of the APOGEE survey is providing near-infrared (near-IR), high-resolution, high signal-to-noise spectra of stars in the halo, disc, bar, and bulge of the Milky Way. The near-IR spectral window is especially important in the study of the Galactic bulge, where stars are obscured by the dust and gas of the disc in its line of sight. We present a chemical characterization of the globular cluster NGC 6544 with high-resolution spectroscopy. The characterization of the cluster chemical fingerprint, given its status of 'interloper' towards the Galactic bulge and clear signatures of tidal disruption in its core is crucial for future chemical tagging efforts. Cluster members were selected from the DR16 of the APOGEE survey, using chemodynamical criteria of individual stars. A sample of 23 members of the cluster was selected. An analysis considering the intracluster abundance variations, known as anticorrelations is given. According to the red giant branch (RGB) content of the cluster, the iron content and α-enhancement are [Fe/H] = −1.44 ± 0.04 dex and [α/Fe] = 0.20 ± 0.04 dex, respectively. Cluster members show a significant spread in [Fe/H] and [Al/Fe] that is larger than expected based on measurement errors. An [Al/Fe] spread, signal of an Mg–Al anticorrelation is observed and used to constrain the cluster mass budget, along with C, N, Mg, Si, K, Ca, and Ce element variations discussed. Across all the analysed evolutionary stages (RGB and asymptotic giant branch), about ∼2/3 (14 out of 23) show distinct chemical patterns, possibly associated with second-generation stars.